Paste composition, biodegradable injectable paste and method for producing same
Patent Information
- Application Number
- JP2024548759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-11
- Filing Date
- 2023-03-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-03-07
AI Technical Summary
【0049】 本発明によるペースト組成物から得られる生分解性注射用ペーストは、可溶性でありながら生体適合性、粘着力、粘弾性のバランスを提供することができるという効果がある。
Smart Images

Figure 2025506539000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a paste composition, a biodegradable injectable paste obtained therefrom, and a method for producing the same. More specifically, the present invention relates to a paste composition that provides a hydrogel bonded by crosslinking as a paste phase using the paste composition, thereby providing the convenience of being able to apply the paste to an application site using a single syringe and providing a balance of biocompatibility, adhesive strength, and viscoelasticity, a biodegradable injectable paste obtained therefrom, and a method for producing the same. [Background technology]
[0002] Hydrogels are three-dimensional structures consisting of a network of hydrophilic molecules, most of whose components are composed of water. Hydrogels have the properties of high water content, porous structure, and biocompatibility.
[0003] Hydrogels can exhibit a variety of properties depending on the type of polymer they use as their main chain or the type of crosslinking method they employ.
[0004] Synthetic compounds such as polyacrylic acid polymers and polyvinyl alcohol are less biocompatible but are easily chemically deformable, making engineering applications very easy. On the other hand, natural compounds, especially extracellular matrix (ECM) components such as collagen, fibrin, and hyaluronic acid, are used as the main chain, but are difficult to deform and difficult to engineer. However, because they are derived from living organisms, they have the advantage of being suitable for clinical applications because they have fewer side effects such as immune and inflammatory reactions when transplanted.
[0005] Hyaluronic acid has the structure shown in chemical formula 1 below, and can form hydrogels with various physical properties through covalent bonds.
[0006] [Chemical formula 1] [ka]
[0007] Gelatin is a natural polymer that transforms the triple-helix structure of collagen into a single-helix structure. Gelatin is classified into two types, gelatin A and gelatin B, depending on the processing method. Gelatin A can be produced by acid processing, and gelatin B can be produced by base processing.
[0008] Gelatin is widely used in tissue engineering due to its biocompatibility and ease of processing. Gelatin hydrogels in particular offer many advantages for tissue regeneration due to the ease of delivery of growth factors. However, gelatin hydrogels also have the disadvantage of having poor mechanical strength.
[0009] As mentioned above, hydrogels have a high water content and are physicochemically similar to the extracellular matrix, making them highly biocompatible. For this reason, hydrogels are being considered for various applications in the medical and pharmaceutical fields.
[0010] However, hydrogels have poor mechanical properties, particularly low tensile strength, which limits their application to areas that must withstand load. As a result, they suffer from the problem of quickly dissolving at the target site and disappearing in a short period of time.
[0011] In Korean Patent Publication No. 2017-7032839, which is a related prior art, an attempt was made to provide mechanical properties as well as viscoelasticity by PEGylating linear or branched multi-armed poly(ethylene glycol) (PEG) using a multifunctional reactor.
[0012] However, this requires freezing, drying, grinding, and rehydration to convert into microgel particles that can provide a balance of viscoelasticity, so there is still a need to develop biodegradable injectable pastes that are soluble yet provide a balance of biocompatibility, adhesion, and viscoelasticity.
[0013] Furthermore, injectable hydrogels are cross-linked three-dimensional polymers that contain a significant amount of water, and therefore have excellent biocompatibility and biodegradability, making them widely used.
[0014] For example, when used as a drug support, the injectable hydrogel (such as a dry powder type) and a drug solution are mixed using two syringes and applied to the surgical site, etc. Summary of the Invention [Problem to be solved by the invention]
[0015] The technical problem to be solved by the present invention is to provide a paste composition that uses a hydrogel bonded by crosslinking, provides the convenience of being able to be applied to an application site such as a surgical site using a single syringe without the need to mix medicinal solutions, and can provide a balance of biocompatibility, adhesive strength, and viscoelasticity.
[0016] Furthermore, the present invention provides a biodegradable paste for injection using the paste composition and a method for producing the same.
[0017] The above and other objects of the present invention can be achieved by the present invention described below. [Means for solving the problem]
[0018] In order to achieve the above object, the present invention provides a biodegradable injectable paste composition for controlled modification (adjustment of water content) of crosslinked products between a polymer and a monomer having a biodegradable unit, the composition comprising two or more backbone polymers, a diglycidyl ether monomer, an active ingredient or a mixture thereof, and a carrier, the two or more backbone polymers, the diglycidyl ether monomer, the active ingredient or a mixture thereof being uniformly dispersed in the carrier, the backbone polymer or the active ingredient forming a support skeleton comprising an adhesive polymer having a single-helix structure, and the carrier not reacting with the backbone polymer, the diglycidyl ether monomer, and the active ingredient.
[0019] The carrier may be contained in an amount of 80% by weight or more based on the total weight of the two or more backbone polymers, the adhesive polymer having a single helical structure, the diglycidyl ether monomer, the active ingredient and the carrier.
[0020] The adhesive polymer having a single helix structure may be obtained by converting the triple helix structure of collagen into a single helix structure.
[0021] The adhesive polymer having a single helix structure may be a polymer that dissolves under basic or acidic conditions.
[0022] When the adhesive polymer having a single helical structure is included in a first backbone polymer among the two or more backbone polymers, a support skeleton may be formed by a bond between the adhesive polymer having a single helical structure and the first backbone polymer.
[0023] When the adhesive polymer having a single helix structure is included in the active ingredient, a support skeleton may be formed by the bond between the first backbone polymer and the second backbone polymer.
[0024] The first backbone polymer may be a hyaluronic acid-based or natural polymer selected from the group consisting of hyaluronic acid, hyaluronates, collagen, gelatin, chitosan, starch, alginic acid and alginates.
[0025] The second backbone polymer may be a cellulosic or synthetic polymer selected from the group consisting of carboxymethylcellulose, cellulose, polyvinylpyrrolidone, poloxamer, polyvinyl alcohol, and polyethylene glycol, excluding species overlapping with the first backbone polymer.
[0026] The active ingredient contained in the first backbone polymer or the second backbone polymer is one or more selected from starch, collagen, chitosan, carboxymethylcellulose, sodium hyaluronate, polyvinylpyrrolidone, poloxamer, polyethylene glycol, thrombin, fibrin, fibrinogen, tannic acid, vitamin K, bovine serum albumin (BSA), gentamicin, hemostatic agents, calcium chloride, drug delivery agents, wound dressings, skin soothing agents, moisturizing agents, anti-inflammatory agents, atopic treatment agents, and natural product active ingredients, excluding those overlapping with the first backbone polymer or the second backbone polymer.
[0027] The carrier may be provided as phosphate buffered saline, purified water, water for injection, or physiological saline.
[0028] In the components constituting the paste composition, the weight ratio of the adhesive polymer having a single helix structure: two or more types of backbone polymers (total amount of two or more types): diglycidyl ether monomer: carrier: active ingredient may be 0.1-15:0.05-7:0.00001-5:82-95:0-0.9.
[0029] The present invention also provides a biodegradable injectable paste obtained from the paste composition, the paste being provided in the form of microhydrogel particles that maintain viscoelastic balance by including two or more types of backbone polymers, a diglycidyl ether monomer, an active ingredient, and a carrier, and by including an adhesive polymer having a single helix structure in the backbone polymer or the active ingredient, the carrier is included in an amount of 80% by weight or more based on the total weight of the backbone polymer, the diglycidyl ether monomer, the active ingredient, and the carrier, and the paste is in the form of a paste that can be applied to an application site using a single syringe.
[0030] The size of the microhydrogel particles may be from 100 to 600 μm.
[0031] The biodegradable injectable paste may be a wet powder having an average particle size of 50 to 400 μm, and the pressing force (injection force or extrusion force) measured by filling a 10 ml injection container with 1 to 7 ml of the wet powder and using a universal tensile tester may be 40 N or less, preferably 30 N or less.
[0032] The biodegradable injectable paste may contain an adhesive polymer powder and have an adhesive strength of 5N or more, preferably 9N or more, as measured by an adhesive strength test using a rheometer.
[0033] Alternatively, 10 ml of water may be added to 0.2 g of a sample, and the weight may be measured after a certain period of time at 37° C. and 50 rpm to confirm the water absorption capacity, and the water content measured using a moisture meter may be 80 to 95%.
[0034] In addition to water absorption, the biodegradable injectable paste was also measured for blood absorption and time. An appropriate amount of blood was dropped onto the sample, and the sample was rotated 180° every 10 seconds to measure blood absorption and time. Next, after measurement using a microplate reader based on the blood coagulation index test method, the blood coagulation index (BCI) calculated by the following formula 1 may be 70% or more, preferably 74% or more.
[0035] [Formula 1] BCI(%)=100-((D o / D s )×100) (Here, D s means the absorbance of the hemoglobin solution, and D o means the absorbance of hemolyzed whole blood. The BCI value indicates the blood coagulation degree, and the higher the BCI value, the better the coagulation performance.)
[0036] The biodegradable injectable paste may have a complex viscosity of 3,000,000 cP or more, preferably 10,000,000 cP or more, measured at 0.1 Hz using a rheometer under conditions of spindle P25, sample weight of 0.5 g.
[0037] The biodegradable injectable paste was subjected to an in vitro decomposition test using a decomposition enzyme, and the degree of decomposition was examined over time in a shaking incubator at 37°C at 100 rpm. It was confirmed that the paste was almost completely decomposed after 48 hours.
[0038] The present invention further provides a method for producing a biodegradable injectable paste, comprising: a first step of preparing a first backbone polymer and adding it to a basic substance to prepare a base formulation; a second step of preparing a porous support by introducing the base formulation into a diglycidyl ether monomer and crosslinking the polymer; and a third step of purifying and pulverizing the porous support to obtain a biodegradable injectable paste and binding an active ingredient to the surface thereof, wherein the base formulation or the biodegradable injectable paste contains an adhesive polymer having a single helix structure that is soluble under basic conditions, and is provided in the form of a wet paste due to the carrier provided during purification.
[0039] The basic substance used in the first step may be 0.1-1N sodium, potassium, or calcium hydroxide, preferably 0.1-0.5N sodium hydroxide.
[0040] The active ingredient contained in the first backbone polymer or the second backbone polymer is one or more selected from starch, collagen, chitosan, carboxymethylcellulose, sodium hyaluronate, polyvinylpyrrolidone, poloxamer, polyethylene glycol, thrombin, fibrinogen, tannic acid, vitamin K, bovine serum albumin (BSA), gentamicin, hemostatic agents, calcium chloride, drug delivery agents, wound dressings, skin soothing agents, moisturizers, anti-inflammatory agents, atopic treatment agents, and natural product active ingredients, preferably excluding species overlapping with those in the first backbone polymer or the second backbone polymer.
[0041] The carrier is preferably provided as phosphate buffered saline, purified water, water for injection, or physiological saline.
[0042] It is preferable that two or more types of backbone polymers, diglycidyl ether monomers, active ingredients, or mixtures thereof are uniformly dispersed in the carrier, the backbone polymers or active ingredients form a support skeleton containing an adhesive polymer having a single-helix structure, and the carrier does not react with any of the backbone polymers, diglycidyl ether monomers, and active ingredients.
[0043] In the components constituting the biodegradable paste composition, the weight ratio of adhesive polymer having a single helix structure: two or more types of backbone polymers (total amount of two or more types): diglycidyl ether monomer: carrier: active ingredient is preferably 0.1-15:0.05-7:0.00001-5:82-95:0-0.9.
[0044] It is preferable that the carrier is contained in an amount of 80% by weight or more based on the total weight of the two or more backbone polymers, the adhesive polymer having a single helical structure, the diglycidyl ether monomer, the active ingredient and the carrier.
[0045] The adhesive polymer having a single helix structure is preferably one obtained by converting the triple helix structure of collagen into a single helix structure.
[0046] When the adhesive polymer having a single helical structure is included in a first backbone polymer among the two or more backbone polymers, it is preferable that a support skeleton is formed by a bond between the adhesive polymer having a single helical structure and the first backbone polymer.
[0047] When the adhesive polymer having a single helix structure is contained in the active ingredient, it is preferred that the support skeleton is formed via a bond between the first backbone polymer and the second backbone polymer.
[0048] In the third step, the porous support can be neutralized while removing residual crosslinker by repeating purification up to nine times using phosphate buffered saline, purified water, water for injection, or saline, and then pulverized to an average particle size in the range of 50 to 500 μm. Effect of the Invention
[0049] The biodegradable injectable paste obtained from the paste composition according to the present invention has the effect of being soluble while providing a balance of biocompatibility, adhesive strength, and viscoelasticity.
[0050] In particular, the biodegradable injectable paste according to the present invention provides a soluble wettable powder uniformly distributed in a carrier, and is applicable to applications such as hemostatic agents, bone fillers, wound dressings, drug delivery systems, tissue repair materials, skin soothing agents, moisturizers, anti-inflammatory agents, and atopic treatment agents. [Brief description of the drawings]
[0051] [Figure 1] 1 is a diagram showing the properties of a product according to embodiment 1 of the present invention, in which the microscope photograph on the right is a 1 mm radius image, and the black spots in the microscope photograph on the right indicate air bubbles. [Diagram 2] 1 is a photograph of the product according to embodiment 1 of the present invention after a blood absorption test, and the microscope photograph on the right is a view of a radius of 1 mm. As shown in the microscope photograph on the right, it can be seen that blood is well absorbed between the paste. [Diagram 3] 1 is a SEM image of the product after drying according to embodiment 1 of the present invention. As shown in the image, porous beads can be seen. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0052] The paste composition, the biodegradable injectable paste and the method for producing the same of the present invention will be described in detail below.
[0053] The present inventors have been researching a biodegradable injectable paste that can be applied using one syringe, without the need to mix medicinal solutions using two syringes and apply them to a surgical site, and that is soluble yet has a balance of biocompatibility, adhesiveness, and viscoelasticity.The inventors have confirmed that all of the above-mentioned objects can be achieved by using a paste composition provided in the form of a wet paste containing a natural polymer having a specific structure in the skeleton or on the surface and a non-dried powder that has been crosslinked and purified with a specific crosslinking agent. Based on this, the inventors have continued their research and have completed the present invention.
[0054] Paste Composition In one embodiment of the present invention, the paste composition refers to a composition for controlled modification (water content adjustment) of cross-linking bonds between polymers and monomers having biodegradable units.
[0055] The paste composition comprises two or more types of backbone polymers, diglycidyl ether monomers, active ingredients or mixtures thereof; and a carrier; wherein the two or more types of backbone polymers, diglycidyl ether monomers, active ingredients or mixtures thereof are uniformly dispersed in the carrier, and the backbone polymer or active ingredient comprises an adhesive polymer having a single-helix structure and forms a support skeleton.
[0056] The carrier is characterized by not reacting with any of the backbone polymer, the diglycidyl ether monomer, and the active ingredient. In this case, there is no need to use two syringes to mix the medicinal solutions and apply them to the surgical site, etc.; the mixture can be applied using a single syringe, and a biodegradable injectable paste can be provided that is soluble yet has a balance of biocompatibility, adhesive strength, and viscoelasticity.
[0057] In one embodiment of the present invention, the paste composition includes as one of its most important characteristics wettability.
[0058] The term "wettable" refers to a state in which the moisture content is 80% or more in excess as measured using a moisture meter, unless otherwise specified.
[0059] In order to achieve the above-mentioned wettability, in one embodiment of the present invention, the carrier may be 80% by weight or more, specifically in the range of 82 to 95% by weight, based on the total weight of the two or more backbone polymers, the adhesive polymer having a single helix structure, the diglycidyl ether monomer, the active ingredient, and the carrier. If it is within this range, even if it contains excess moisture, the decomposition rate will not decrease and it can maintain a stable state until application.
[0060] The adhesive polymer having a single-helix structure may be a collagen triple-helix structure modified into a single-helix structure.
[0061] As the adhesive polymer having a single helix structure, a polymer that dissolves under acidic conditions can be used, but it is preferable to use a polymer that dissolves under basic conditions as much as possible, since this makes it easier to control the reaction.
[0062] When the adhesive polymer having a single helical structure is included in the first backbone polymer among the two or more backbone polymers, a support skeleton can be formed by the bond between the adhesive polymer having a single helical structure and the first backbone polymer.
[0063] When the adhesive polymer having a single helix structure is included in the active ingredient, a support framework can be formed by the bond between the first backbone polymer and the second backbone polymer.
[0064] The first backbone polymer may be a hyaluronic acid-based or natural polymer selected from the group consisting of hyaluronic acid, hyaluronates, collagen, gelatin, chitosan, starch, alginic acid and alginates.
[0065] The second backbone polymer may be a cellulosic or synthetic polymer selected from the group consisting of carboxymethylcellulose, cellulose, polyvinylpyrrolidone, poloxamer, polyvinyl alcohol, and polyethylene glycol, excluding species overlapping with the first backbone polymer described above.
[0066] The diglycidyl ether monomer may be, but is not limited to, an alkanediol diglycidyl ether having 1 to 8 carbon atoms. In this case, crosslinking between backbone polymers can be efficiently performed without deteriorating the mechanical properties of the backbone polymer.
[0067] The active ingredient may be one or more selected from the group consisting of starch, collagen, chitosan, carboxymethylcellulose, sodium hyaluronate, polyvinylpyrrolidone, poloxamer, polyethylene glycol, thrombin, fibrinogen, tannic acid, vitamin K, bovine serum albumin (BSA), gentamicin, hemostatic agents, calcium chloride, drug delivery agents, wound dressings, skin soothing agents, moisturizers, anti-inflammatory agents, atopic treatment agents, and natural active ingredients.
[0068] The carrier may be provided as phosphate buffered saline, purified water, water for injection, or saline, and as described above, is preferably 80% by weight or more, specifically 82 to 95% by weight, based on the total content of the backbone polymer, diglycidyl ether monomer, active ingredient, and water, in order to exhibit excessive wettability.
[0069] In the components constituting the biodegradable injectable paste, when the weight ratio of adhesive polymer having a single helical structure:backbone polymer (polymer excluding adhesive polymer having a single helical structure when it is included in the backbone polymer):diglycidyl ether monomer:water:active ingredient is, for example, 0.1-15:0.05-7:0.00001-5:82-95:0-0.9, the paste has the effect of being soluble while having an excellent balance of biocompatibility, adhesive strength, and viscoelasticity.
[0070] In the components constituting the paste composition, when the weight ratio of adhesive polymer having a single helix structure: two or more types of backbone polymer: diglycidyl ether monomer: water: active ingredient is, for example, 0.1-15:0.05-7:0.00001-5:82-95:0-0.9, and specifically 0.15-14:0.3-6.6:0.00001-5:84-93:0.1-0.35, the composition has the effect of being soluble yet having an excellent balance of biocompatibility, adhesive strength, and viscoelasticity.
[0071] <Biodegradable injectable paste> In one embodiment of the present invention, the biodegradable injectable paste is preferably obtained from a paste composition for controlled modification (water content adjustment) of cross-linked products between polymers and monomers having biodegradable units as described above.
[0072] As an example, the biodegradable injectable paste is provided in the form of microhydrogel particles that contain two or more types of backbone polymers, a diglycidyl ether monomer, an active ingredient, and a carrier, and that maintains viscoelastic balance by incorporating an adhesive polymer having a single helix structure in the backbone polymer or the active ingredient, and is characterized in that the carrier is contained in an amount of 80% by weight or more based on the total weight of the backbone polymer, the diglycidyl ether monomer, the active ingredient, and the carrier, and is in the form of a paste that can be applied to the application site using a single syringe.In this case, it has the effect of being soluble yet having an excellent balance of biocompatibility, adhesive strength, and viscoelasticity.
[0073] The size of the microhydrogel particles may be, for example, 100 to 600 μm, specifically 200 to 400 μm, in which case the optimum maximum effect on water absorption is obtained.
[0074] The biodegradable injectable paste is a non-dried powder having an average particle size of 50 to 400 μm, specifically 100 to 400 μm, and preferably 200 to 400 μm, and is characterized in that a drying process is omitted in order to provide excessive wettability.
[0075] When the particle has the above average particle size, the production is easy and the blood absorption capacity is excellent. The average particle size can be measured by SEM image analysis.
[0076] The biodegradable injectable paste may have a syringe pressure (injection force or elastic force) of 5 times or less, specifically within a range of 1 to 4 times, of the adhesive force. In this case, the paste is easy to use and adheres well to the application site, thereby enhancing efficacy.
[0077] The injection force can be measured by a universal tensile tester using a 10 ml injection container.
[0078] The adhesive strength can be measured using a rheometer.
[0079] The biodegradable injectable paste is subjected to the following steps: blood is dropped onto a specimen, and immediately after the passage of a standing time a, the specimen is inverted 180° to measure the presence or absence of blood absorption and the time. The paste is made to absorb water in accordance with an absorbency test to measure the amount of water absorbed. After measurement using a microplate reader based on a blood coagulation index confirmation test, the blood coagulation index (BCI) calculated by the following formula 1 can be 70% or more, preferably 74% or more.
[0080] [Formula 1] BCI(%)=100-((D o / D s )×100)
[0081] (Here, D s means the absorbance of the hemoglobin solution, and D o BCI value indicates the absorbance of hemolyzed whole blood. The BCI value indicates the blood coagulation degree, and the higher the BCI value, the better the coagulation performance. After applying 0.2ml of blood to a 0.2g specimen, the specimen was turned 180 degrees at 10 second intervals, and the time it took for all the blood to be absorbed and fall off was measured. Water absorption was confirmed by adding 10ml of water to a 0.2g specimen and measuring the weight after 24 hours at 37℃ and 50 rpm.
[0082] The biodegradable injectable paste may have a moisture content of 80% or more, specifically 80 to 95%, as measured with a moisture meter. In this case, it is preferable because it can be directly applied to the application site, such as the surgical site, using one syringe, without the need to mix the medicinal solutions using two syringes.
[0083] The biodegradable injectable paste may have a complex viscosity of 3,000,000 cP or more, preferably 9,000,000 cP or more, measured at 0.1 Hz using a rheometer under conditions of spindle P25, sample weight of 0.5 g.
[0084] The biodegradable injectable paste may have a cell viability of 80% or more, preferably 89% or more, as measured based on ISO 10993-Cytotoxicity Measurement Method.
[0085] The biodegradable injectable paste has the effect that no bacteria are detected as a result of measurement based on the sterility test method of the Korean Pharmacopoeia.
[0086] The biodegradable injectable paste has the effect of being non-cytotoxic as measured based on a cytotoxicity test method.
[0087] The biodegradable injectable paste has an effect that the residual amount of the crosslinking agent is 1% by weight or less as a result of confirming the residual amount of the crosslinking agent by the internal standard method using a GC chromatography device.
[0088] <Method of manufacturing biodegradable paste for injection> A method for producing a biodegradable injectable paste according to one embodiment of the present invention includes a first step of preparing a base formulation, a second step of producing a support, and a third step of obtaining a biodegradable injectable paste.
[0089] Specifically, in the first step, a first backbone polymer may be prepared and added to a basic substance to prepare a base formulation.
[0090] The first backbone polymer may include an adhesive polymer having a single helix structure that is soluble under basic conditions, which can provide an effect of preparing a paste with an appropriate moisture content and maintaining its shape.
[0091] When the backbone polymer contains an adhesive polymer having a single helix structure that is soluble under basic conditions, the additional polymer corresponding to the remaining backbone polymer may be a hyaluronic acid-based or natural polymer selected from the group consisting of hyaluronic acid, hyaluronate, collagen, gelatin, chitosan, starch, alginic acid and alginate, in which case a synergistic effect between the extrusion force and the adhesive force can be provided.
[0092] When the first backbone polymer does not include an adhesive polymer having a single helix structure that is soluble under basic conditions, the two or more backbone polymers may include the first backbone polymer and a second backbone polymer different from the first backbone polymer, where the second backbone polymer may be a cellulosic or synthetic polymer selected from the group consisting of carboxymethylcellulose, cellulose, polyvinylpyrrolidone, poloxamer, polyvinyl alcohol, and polyethylene glycol, excluding species overlapping with the first backbone polymer.
[0093] Furthermore, the first backbone polymer and the second backbone polymer may contain an active ingredient, if necessary, which is one or more selected from starch, collagen, chitosan, carboxymethylcellulose, sodium hyaluronate, polyvinylpyrrolidone, poloxamer, polyethylene glycol, thrombin, fibrin, fibrinogen, tannic acid, vitamin K, bovine serum albumin (BSA), gentamicin, hemostatic agents, calcium chloride, drug delivery agents, wound dressings, skin soothing agents, moisturizing agents, anti-inflammatory agents, atopic treatment agents, and natural product active ingredients, excluding those overlapping with the first backbone polymer or the second backbone polymer.
[0094] The basic substance used in the first step may contain an alkali metal such as sodium, potassium, or calcium at 0.1 to 0.5 N. In this case, the dissolving power of the base preparation can be increased, which is preferable.
[0095] In the second step, the base formulation can be introduced into a diglycidyl ether monomer and crosslinked to produce a porous support.
[0096] The third step is to purify and pulverize the porous support to obtain a biodegradable injectable paste, and to bind an active ingredient to the surface.
[0097] The biodegradable injectable paste may include an adhesive polymer having a single helix structure that is soluble under basic conditions.
[0098] In the third step, the porous support can be neutralized while removing residual crosslinker by repeating purification up to nine times using phosphate buffered saline, purified water, water for injection, or saline, and then pulverized to an average particle size in the range of 50 to 500 μm.
[0099] The biodegradable injectable paste can be provided in the form of a wet paste by the water provided during the purification.
[0100] In particular, when the biodegradable injectable paste of the present invention is used as a hemostatic agent, the hemostatic ability is improved together with the active ingredient, and the paste can exhibit excellent performance as a hemostatic agent.
[0101] In particular, when the biodegradable injectable paste of the present invention is used as a bone filler, the physical properties are improved together with the active ingredient, and the paste can exhibit excellent performance as a bone filler.
[0102] That is, the biodegradable injectable paste according to one embodiment of the present invention is provided in a state in which it is uniformly dispersed in a carrier, and is suitable for use as a hemostat, bone filler, wound dressing, drug delivery medium, tissue repair material, skin soothing agent, moisturizer, anti-inflammatory agent, atopic treatment agent, etc.
[0103] In the following, preferred examples will be described to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0104] [Example: Production of biodegradable injectable paste] Example 1 As a paste composition of Example 1, gelatin and sodium hyaluronate were prepared.
[0105] Specifically, 30% by weight of the gelatin and 0.84% by weight of sodium hyaluronate were mixed and dissolved in 0.25N NaOH.
[0106] The melt was charged with 0.84 wt % of 1,4-butanediol diglycidyl ether and crosslinked at 30° C. for 18 hours to prepare a support backbone.
[0107] The crosslinked product was purified by repeatedly using phosphate buffered saline 8 to 9 times to remove residual butanediol diglycidyl ether and neutralize the pH.
[0108] The resulting biodegradable injectable paste consisted of 13.64% by weight gelatin, 0.38% by weight sodium hyaluronate, 0.0002% by weight 1,4-butanediol diglycidyl ether, and 85.84% by weight phosphate buffered saline.
[0109] The phosphate buffered saline used here was a mixture of 84.87% by weight of purified water, 0.71% by weight of sodium chloride, 0.04% by weight of potassium dihydrogen phosphate, and 0.22% by weight of sodium phosphate dibasic dodecahydrate.
[0110] The biodegradable injectable paste was then ground using a plunger mill to an average particle size of 300 μm.
[0111] Thereafter, 0.14% by weight of calcium chloride dihydrate was mixed with the pulverized material, thereby producing a biodegradable injectable paste having the active ingredient bonded to its surface.
[0112] Example 2 As the paste composition of Example 1, sodium hyaluronate and carboxymethyl cellulose were prepared.
[0113] Specifically, 15.24% by weight of sodium hyaluronate and 7.62% by weight of carboxymethylcellulose were mixed and dissolved in 25N NaOH.
[0114] 0.95 wt % of 1,4-butanediol diglycidyl ether was added to the dissolved material, and crosslinked at 30° C. for 18 hours to prepare the backbone of the support.
[0115] The crosslinked product was purified by repeatedly using phosphate buffered saline 8 to 9 times to remove residual butanediol diglycidyl ether and neutralize the pH.
[0116] After purification, the prepared biodegradable injectable paste consisted of 4.32% by weight sodium hyaluronate, 2.16% by weight carboxymethylcellulose, 0.0002% by weight 1,4-butanediol diglycidyl ether, and 93.18% by weight phosphate buffered saline.
[0117] The biodegradable injectable paste was then pulverized using a plunger mill to an average particle size of 300 μm.
[0118] Thereafter, the ground material was mixed with 0.14% by weight of calcium chloride dihydrate and 0.2% by weight of gelatin to produce a biodegradable injectable paste having the active ingredient bonded to its surface.
[0119] Example 3 A paste-like biodegradable injection was prepared by repeating the same steps as in Example 1, except that gelatin was further used in an amount equal to the calcium chloride dihydrate content in Example 1, and calcium chloride dihydrate was not added.
[0120] Example 4 A biodegradable paste for injection was prepared by repeating the same process as in Example 2, except that gelatin was further used in an amount equal to the calcium chloride dihydrate content in Example 2, and calcium chloride dihydrate was not added.
[0121] Comparative Example 1 An attempt was made to prepare a paste-like biodegradable injectable paste by repeating the same process as in Example 1, except that the same amount of sodium hyaluronate as that of gelatin in Example 1 was further used and gelatin was not included, but a paste-like bead shape could not be prepared.
[0122] Comparative Example 2 A biodegradable paste for injection was prepared by repeating the same process as in Example 1, except that gelatin was used in an amount equal to the amount of sodium hyaluronate in Example 1, and sodium hyaluronate was not used.
[0123] Comparative Example 3 A biodegradable paste for injection was prepared by repeating the same process as in Example 1, except that 10% by weight of gelatin was mixed in the same manner as in Example 1.
[0124] Comparative Example 4 A biodegradable paste for injection was prepared by repeating the same process as in Example 2, except that sodium hyaluronate in Example 2 was omitted and only carboxymethylcellulose was used.
[0125] Comparative Example 5 A paste-like hyaluronic acid crosslinked body was produced by repeating the same steps as in Example 1, except that polyethylene glycol diacrylate (PEGDA) was used instead of 1,4-butanediol diglycidyl ether in Example 1.
[0126] Comparative Example 6 A biodegradable paste for injection was prepared by repeating the same steps as in Example 1, except that freeze-drying was carried out after purification and pulverization in Example 1.
[0127] Reference example 1 A biodegradable injectable paste in a paste phase was prepared by repeating the same process as in Example 1, except that the pulverized size was changed from an average particle size of 300 μm to an average particle size of 700 μm.
[0128] Reference example 2 An attempt was made to produce a paste-like biodegradable injectable paste by repeating the same process as in Example 1, except that the crushing size in Example 1 was changed from an average particle size of 300 μm to an average particle size of 30 μm. However, the mesh size of the grinder was too small, so a sample could not be produced.
[0129] Test Example The pastes produced in Examples 1 to 4, Comparative Examples 2 to 6, and Reference Example 1 were subjected to complex viscosity (complex viscosity), adhesive strength, injectability, hemostatic performance (blood absorption capacity), blood coagulation index (BCI), cytotoxicity test, and sterility test as described below, and the measurement results are shown in Table 1 below.
[0130] <Physical property measurement method> *Complex viscosity: Based on the complex viscosity measurement method, the complex viscosity was measured at 0.1 Hz using a rheometer under the conditions of spindle P25 and 0.5 g of sample.
[0131] *Adhesive strength: Based on the tack test method, under the conditions of spindle P25 and sample 0.5 g, the test liquid was pressed with a constant force (1 N) and then raised at a speed of 1.25 mm / min. The maximum force was measured using a rheometer.
[0132] *Injection force: Based on the injectability test, it was measured using a universal material testing machine at a speed of 1 mm / s.
[0133] *Hemostatic performance (blood absorption capacity): Blood was dropped onto the specimen, and if the blood did not fall immediately, it was recorded as 0 seconds. If the blood did not fall immediately, the specimen was turned 180° every 10 seconds and checked to see if it fell until 60 seconds.
[0134] *Blood Coagulation Index (BCI): Measured using a microplate reader based on the BCI test method.
[0135] *Cytotoxicity: Measured based on the cytotoxicity test method, and expressed as % cell viability.
[0136] *Sterility test: The presence or absence of bacteria was confirmed based on the sterility test method, and the results were expressed as presence or absence.
[0137] *Moisture content (moisture content): The moisture content of the test specimen was measured using a moisture meter.
[0138] [Table 1]
[0139] As shown in Table 1 above, in Examples 1 to 4 corresponding to the biodegradable injectable paste of the present invention, appropriate ranges were provided for all measurement items including complex viscosity, adhesive strength, injectability, blood absorption capacity, blood coagulation index (BCI), cytotoxicity, sterility test and water content, and the effect of providing a balance between biocompatibility, adhesive strength and viscoelasticity while being soluble was obtained.
[0140] On the other hand, in Comparative Examples 1 to 6, which do not correspond to the biodegradable injectable paste of the present invention, it was confirmed that production was impossible or that even if production was possible, the adhesive strength, absorbency, extrusion force, etc. were insufficient.
[0141] Specifically, in Comparative Example 1, in which the same amount of the first backbone polymer as the adhesive polymer was used and no adhesive polymer was used, the adhesive strength was insufficient and a paste could not be produced.
[0142] In addition, in Comparative Example 2, in which the adhesive polymer was used in an amount equal to the first backbone polymer content, a decrease in adhesive strength was observed.
[0143] Furthermore, in Comparative Example 3, in which the adhesive polymer was inappropriately and excessively added, and in Comparative Example 4, in which the second backbone polymer was used alone, a decrease in absorbency was confirmed.
[0144] Moreover, in Comparative Example 5, in which polyethylene glycol diacrylate was used as the crosslinking agent, unlike the previously used crosslinking agents, high cytotoxicity was confirmed.
[0145] Moreover, in Comparative Example 6, in which the obtained paste-like material was processed into a dry powder type, it was confirmed that the extrusion force was relatively high and the processability was poor.
[0146] Furthermore, if the obtained paste was crushed into excessively large pieces, the absorbency was poor, as shown in Reference Example 1, and if the obtained paste was crushed into excessively small pieces, production was impossible, as shown in Reference Example 2.
[0147] Therefore, when using the biodegradable injectable paste provided in the form of a wet paste containing a non-dried powder that contains a natural polymer having a specific structure in the skeleton or surface of the present invention and is crosslinked with a specific crosslinking agent and purified, the biodegradable injectable paste is provided in a state where it is uniformly dispersed in the carrier, and therefore can be suitably used for applications such as hemostatic agents, bone fillers, wound dressings, drug delivery vehicles, tissue repair materials, skin soothing agents, moisturizers, anti-inflammatory agents, and atopic treatment agents.
Claims
1. A composition for the controlled modification (adjustment of water content) of crosslinked polymers having biodegradable units and monomers, comprising: The composition comprises two or more backbone polymers, diglycidyl ether monomers, active ingredients or mixtures thereof, and a carrier; The two or more backbone polymers, the diglycidyl ether monomer, the active ingredient or a mixture thereof are uniformly dispersed in the carrier, the backbone polymer or the active ingredient comprises an adhesive polymer having a single helix structure to form a support skeleton, and the carrier does not react with the backbone polymer, the diglycidyl ether monomer and the active ingredient.
2. The paste composition according to claim 1, characterized in that the carrier is contained in an amount of 80% by weight or more based on the total weight of the two or more backbone polymers, the adhesive polymer having a single helix structure, the diglycidyl ether monomer, the active ingredient and the carrier.
3. 2. The paste composition according to claim 1, wherein the adhesive polymer having a single helix structure is obtained by converting a triple helix structure of collagen into a single helix structure.
4. The paste composition according to claim 1, characterized in that when the adhesive polymer having a single helical structure is included in a first backbone polymer among the two or more backbone polymers, a support skeleton is formed by a bond between the adhesive polymer having a single helical structure and the first backbone polymer.
5. The paste composition according to claim 1, wherein when the adhesive polymer having a single helix structure is contained in the active ingredient, a support skeleton is formed by the bond between the first backbone polymer and the second backbone polymer.
6. The paste composition according to claim 1, wherein the first backbone polymer is a hyaluronic acid-based or natural polymer selected from the group consisting of hyaluronic acid, hyaluronate, collagen, gelatin, chitosan, starch, alginic acid, and alginate.
7. 2. The paste composition of claim 1, wherein the second backbone polymer is a cellulosic or synthetic polymer selected from the group consisting of carboxymethylcellulose, cellulose, polyvinylpyrrolidone, poloxamer, polyvinyl alcohol, and polyethylene glycol, excluding species overlapping with the first backbone polymer.
8. 2. The paste composition according to claim 1, wherein the active ingredient is one or more selected from the group consisting of starch, collagen, chitosan, carboxymethylcellulose, sodium hyaluronate, polyvinylpyrrolidone, poloxamer, polyethylene glycol, thrombin, fibrinogen, tannic acid, vitamin K, bovine serum albumin (BSA), gentamicin, hemostatic agents, calcium chloride, drug delivery agents, wound dressings, skin soothing agents, moisturizing agents, anti-inflammatory agents, atopic treatment agents, and natural product active ingredients, excluding those overlapping with the first backbone polymer or the second backbone polymer.
9. The paste composition according to claim 1, wherein the carrier is provided as phosphate buffered saline, purified water, water for injection, or saline.
10. The paste composition according to claim 1, characterized in that, in the components constituting the paste composition, the weight ratio of the adhesive polymer having a single helix structure: the two or more kinds of backbone polymers (total amount of the two or more kinds): the diglycidyl ether monomer: the carrier: the active component is 0.1-15:0.05-7:0.00001-5:82-95:0-0.
9.
11. A biodegradable injectable paste obtained from the paste composition according to any one of claims 1 to 10, The composition comprises two or more backbone polymers, a diglycidyl ether monomer, an active ingredient, and a carrier, A biodegradable injectable paste, characterized in that it is provided in the form of microhydrogel particles that maintain viscoelastic balance by including an adhesive polymer having a single helix structure in the backbone polymer or the active ingredient, contains a carrier in an amount of 80% by weight or more based on the total weight of the backbone polymer, diglycidyl ether monomer, active ingredient and carrier, and is in the form of a paste that can be applied to an application site using a single syringe.
12. The injectable biodegradable paste according to claim 11, characterized in that the size of the microhydrogel particles is 100-600 μm.
13. The biodegradable injectable paste according to claim 11, characterized in that the biodegradable injectable paste is a wet powder having an average particle size of 50 to 400 μm, and a pressing force (injection force or extrusion force) measured by filling a 10 ml injection container with 1 to 7 ml of the wet powder using a universal tensile tester is 40 N or less.
14. The biodegradable injectable paste according to claim 11, comprising an adhesive polymer powder having an adhesive strength of 5N or more as measured by an adhesive strength test using a rheometer.
15. The biodegradable injectable paste according to claim 11, characterized in that the water content of the biodegradable injectable paste is 80 to 95% as measured using a moisture meter after adding 10 ml of water to 0.2 g of a specimen and leaving the mixture at 37°C and 50 rpm.
16. The biodegradable injectable paste comprises: An appropriate amount of blood is dropped onto the specimen, and the specimen is turned 180 degrees every 10 seconds to measure the presence or absence of blood absorption and the time. The biodegradable injectable paste according to claim 11, characterized in that the blood coagulation index (BCI) calculated by the following Equation 1 after measurement using a microplate reader according to a blood coagulation index test method is 70% or more. [Formula 1] BCI(%)=100-((D o / D s )×100) (Here, D s means the absorbance of the hemoglobin solution, and D o means the absorbance of hemolyzed whole blood. The BCI value means the blood coagulation degree, and the higher the BCI value, the better the coagulation performance.)
17. The biodegradable injectable paste according to claim 11, characterized in that the complex viscosity of the biodegradable injectable paste is 3,000,000 cP or more, measured at 0.1 Hz using a rheometer under conditions of a spindle P25, a sample of 0.5 g, and a viscosity of 0.1 Hz.
18. A first step of preparing a first backbone polymer and adding it to a basic substance to prepare a base formulation; a second step of incorporating the base formulation into a diglycidyl ether monomer and crosslinking it with a second backbone polymer to produce a porous support; A third step of purifying and pulverizing the porous support to obtain a biodegradable injectable paste and binding an active ingredient to the surface thereof; Including, The base preparation or the biodegradable injectable paste contains an adhesive polymer having a single helix structure that is soluble under basic conditions; The method for preparing a biodegradable injectable paste according to claim 1, characterized in that the paste is provided in the form of a wet paste by a carrier provided during purification.
Citation Information
Patent Citations
Hyaluronic acid-collagen composite hydrogel for injection and preparation method thereof
CN103333349A
Preparation method of injectable directional conductive hydrogel
CN111423600A
Chitosan and applications thereof
WO2020239591A1
A hybrid hydrogel used as a dermal filler and its production method
WO2020242420A1